Prevention of Crime in the Context of Ethno-Social Relations - Tileubergenov, Yerazak Manapovich; Tuleyev, Serik Turlybekovich; Saduakassov, Sharap Seitkasymovich (International Journal of Criminology and Sociology, 2021)
In this article, the authors examine the importance of crime prevention in the context of ethno-social relations. The problem of interethnic interaction is extremely important for any multi-ethnic state. Interethnic contacts are not always positive, which is why the problem of interethnic conflicts is one of the most important and relevant areas of research in modern social sciences. Ethnic conflicts objectively lie on the line of differences between ethnic groups, the subjective basis of which is ethnic identity. The theory of crime and the ways of its prevention is investigated on the basis of the program-target approach. Throughout the research, the authors come to the conclusion that in order to overcome the crime, it is vital to target the most vulnerable groups and implements special programs. As a result of the targeting approach, the ethno-social tensions could be overcome and minimize the proliferation of crime